Value of Antegrade Mechanical Preparation in Elective Colorectal Surgery. A Randomized Clinical Trial - Lavr V. Arkadiy, Rurik K. Odissey, Feodor W. Kir, Ignatyev I. Vasilyev, Chaykovsky F. Feofil (Open Journal of Physicians and Surgeons, 2024)
Elective colorectal surgery refers to planned surgical procedures performed on the colon and rectum, often to treat conditions such as colorectal cancer, diverticulitis, inflammatory bowel disease, or polyps. These procedures are scheduled in advance and allow for proper patient preparation and optimization of surgical outcomes. Elective colorectal surgeries are typically associated with lower risk compared to emergency colorectal operations. Antegrade mechanical bowel preparation (AMBP) is a method used to cleanse the colon prior to elective colorectal surgery. It involves administering laxatives and enemas in an antegrade (forward) direction, moving from the cecum towards the rectum. AMBP aims to thoroughly evacuate the bowel to facilitate the surgical procedure and potentially reduce postoperative complications. The study aimed to evaluate the clinical value of antegrade mechanical bowel preparation (AMBP) compared to no bowel preparation before elective colorectal surgery. This was a prospective, randomized, single-center trial. 150 patients undergoing elective colorectal resection were randomly assigned to either AMBP or no bowel preparation. The primary outcome was the rate of anastomotic leakage. Secondary outcomes included other postoperative complications, operative time, and blood loss. There was no significant difference in the rate of anastomotic leakage between the AMBP group (6.7%) and the no-preparation group (8%). No significant differences were found in other postoperative complications, operative time, or blood loss. The AMBP group had a significantly higher rate of preoperative defecation compared to the no-preparation group.In conclusion, routine use of AMBP does not provide additional benefits over no bowel preparation for patients undergoing elective colorectal surgery. The authors suggest reconsidering the standard practice of using AMBP, as it may unnecessarily burden patients without improving surgical outcomes. Overall, this well-designed randomized trial provides evidence that AMBP does not confer significant advantages in elective colorectal surgery compared to no bowel preparation.